(untitled) (Journal of the College of Basic Education, 2019)
With increased advance in technology, the need to be in harmony with this advance in the world in order to fulfill the necessities of Iraqi EFL students who have become ambitious for knowledge using technology cannot be ignored. Thus, technology has become a part of teaching tools as well as a support for learning a foreign language. Every day, the students are exposed to the Internet that presents a variety of tools for learning more easily and effectively. At present, Facebook is one of the most commonly used social web sites that influence students’ life in many aspects including education, especially in English language learning. It provides them with more opportunities to be involved in practice English language authentically outside the classroom, to learn consciously and unconsciously and to consolidate their foreign language skills. The present study aims at identifying the pros and cons of using Facebook as a tool for learning English language based on Iraqi EFL students’ perspective. To achieve the aim of the current study, a sample of (30) male and female EFL students were chosen from the 4th year/ College of Basic Education/ Mustansiriyah University during the academic year 2018-2019 and questionnaires were implemented for data collection. The results of the data analysis included their perceptions and pointed out the benefits and criticism related to Facebook and learning English. In the light of the obtained results, some conclusions are drawn and a number of recommendations and suggestions for future studies are stated.